Cell therapy of periodontium: from animal to human? - Trofin, Elena Andreea; Monsarrat, Paul; Kémoun, Philippe (Frontiers in Physiology, 2013)
Periodontitis is a chronic inflammatory disease affecting the soft and hard tissues supporting the teeth, which often leads to tooth loss. Its significant impact on the patient’s general health and quality of life point to a need for more effective management of this condition. Existing treatments include scaling/root planing and surgical approaches but their overall effects are relatively modest and restricted in application. The goal of regenerative therapy of periodontal defects is to enhance endogenous progenitors and thus promote optimal wound healing. Considering that the host or tissue might be defective in the periodontitis context, it has been proposed that grafting exogenous stem cells would produce new tissues and create a suitable microenvironment for tissue regeneration. Thus, cell therapy of periodontium has been assessed in many animal models and promising results have been reported. However, the methodological diversity of these studies makes the conversion to clinical practice difficult. The aim of this review is to highlight the primary requirements to be satisfied before the leap to clinical trials can be made. We therefore review cell therapy applications for periodontal regeneration in animal models and the concerns to be addressed before undertaking human experiments.